Combining native MS approaches to decipher archaeal box H/ACA ribonucleoprotein particle structure and activity. Issue 16 (24th April 2015) - Saliou, Jean‐Michel; Manival, Xavier; Tillault, Anne‐Sophie; Atmanene, Cédric; Bobo, Claude; Branlant, Christiane; Van Dorsselaer, Alain; Charpentier, Bruno; Cianférani, Sarah; Barran, Perdita; Cooper, Helen; Eyers, Claire
<x xml:space="preserve">Abstract</x> Site‐specific isomerization of uridines into pseudouridines in RNAs is catalyzed either by stand‐alone enzymes or by box H/ACA ribonucleoprotein particles (sno/sRNPs). The archaeal box H/ACA sRNPs are five‐component complexes that consist of a guide RNA and the aCBF5, aNOP10, L7Ae, and aGAR1 proteins. In this study, we performed pairwise incubations of individual constituents of archaeal box H/ACA sRNPs and analyzed their interactions by native MS to build a 2D‐connectivity map of direct binders. We describe the use of native MS in combination with ion mobility‐MS to monitor the in vitro assembly of the active H/ACA sRNP particle. Real‐time native MS was used to monitor how box H/ACA particle functions in multiple‐turnover conditions. Native MS also unambiguously revealed that a substrate RNA containing 5‐fluorouridine (f5U) was hydrolyzed into 5‐fluoro‐6‐hydroxy‐pseudouridine (f5ho6Ψ). In terms of enzymatic mechanism, box H/ACA sRNP was shown to catalyze the pseudouridylation of a first RNA substrate, then to release the RNA product (S22f5ho6ψ) from the RNP enzyme and reload a new substrate RNA molecule. Altogether, our native MS‐based approaches provide relevant new information about the potential assembly process and catalytic mechanism of box H/ACA RNPs.